Nutritional status of undergraduate students in the Faculty of Health Sciences at the University of the Free State - Abera, Banchewesen Melaku (University of the Free State, 2006)
The aim of this study was to describe the nutritional status and related lifestyle factors of undergraduate students in the Faculty of Health Sciences at the University of the Free State. A representative sample of 161 (24% male and 76% female) full time students were randomly selected. The median ages of students were 21.8 years for males and 21.4 years for females. Dietary intake, lifestyle and anthropometric variables and associations between the above were determined. Dietary intake was determined by means of a 24-hour recall and short food frequency questionnaire. Weight and height, waist and hip circumference measurement were obtained to calculate body mass index (BMI) and fat distribution. Lifestyle factors included smoking, alcohol consumption, physical activity and socio-demographic status and these were determined by means of a questionnaire. Adequacy of diet was evaluated by comparing the intake of each student to the intake recommended by the Food Guide Pyramid. Almost 44% of students’ daily intake of bread, cereals, rice and pasta was lower than the recommended six servings. Similarly, 98% ate less than three servings of vegetables and 58.4% ate less than two servings of fruits. More than 80% of students ate less than two servings of milk, yoghurt and cheese, while 16.1% ate less than two servings of meat, poultry, fish, dry beans, eggs and nuts. Only 57.1% of students reported consuming small quantities of fats, oils and sweets. Meal patterns showed that a small percentage of students skipped breakfast (7%). Median energy intake of female students (5195kJ) was significantly lower than that of male students (8943kJ). Median energy and fat intake was relatively low, while carbohydrate and protein intakes were slightly higher than recommendations. Anthropometric information included BMI, waist circumference and waist hip ratio (WHR). 22.1% of female and 12.9% of male students were overweight or obese and 10.7% of female and 0% of male students were underweight. Four students had values above cut off points for waist circumference (for females > 88 cm for males > 102 cm) and six students had values above cut off point for waist-hip ratio (for females > 0.8 and for males > 0.9), indicating risk for cardiovascular disease. The physical activity level of the students broadly classified them as very active (59%) and active (39%). However, 68% of the students did not attend gym or participate in any sporting activities. Of the total students, 10.6% were smokers; smoking a median of 3.5 cigarettes per day. The majority of the students (62%) consumed alcohol. The median frequency of alcohol consumption was 4.0 days per month, and on those days (mostly weekend days), the median intake was 3 drinks. A positive association between smoking and alcohol consumption was found. Alcohol consumption was also significantly higher in students residing off-campus. No significant difference in the energy intake of students living on-campus and offcampus was found. Median energy intake of students in the three different BMI categories indicated that overweight/obese students had the highest median energy intake. However, the differences in median energy intake between the three groups were not statistically significant. Students that smoked also tended to be more underweight. A physically active lifestyle with abstention from smoking, moderate alcohol consumption, and consumption of healthy foods maximizes the chance of having a normal weight. Although relatively low, prevalence of obesity in this population needs attention. High BMI values at a young age are independent predictors of being overweight in later years. Being overweight at a young age indicates an increased risk for developing diseases of lifestyle, such as cardiovascular disease. Therefore physical activity and healthy eating habits should be encouraged to prevent obesity and its comorbidities.

Die doel van hierdie studie was om die voedingstatus en leefstylfaktore wat daarmee verband hou van studente in die Fakulteit Gesondheidswetenskappe, Universiteit van die Vrystaat te bepaal. ‘n Verteenwoordige steekproef van 161 (24% manlik en 76% vroulik) voltydse studente is lukraak geselekteer. Die mediaan ouderdom van studente was 21.8 jaar vir mans en 21.4 jaar vir dames. Dieetinname, leefstyl en antropometriese veranderlikes en verbande tussen bogenoemde is bepaal. Dieetinname is deur middel van ‘n 24-uur herroep en kort voedselfrekwensievraelys bepaal. Massa en lengte sowel as middel- en heupomtrek is bepaal om liggaamsmassaindeks (LMI) en vetverspreiding te bereken. Leefstylfaktore het rook, alkoholinname, fisiese aktiwiteit en sosio-demografiese inligting ingesluit wat deur middel van ‘n vraelys ingesamel is. Toereikendhied van die dieet is geëvalueer deur die innames van elke student met die aanbevole innames wat deur die Voedselpiramiede aanbeveel word te vergelyk. Amper 44% van studente se inname van brood, grane, rys en pasta was laer as die aanbevole ses porsies. Amper alle studente (98%) het minder as drie porsies groente geëet en 58.4% het minder as twee porsies vrugte geëet. Meer as 80% van studente het minder as twee porsies melk, jogurt en kaas geëet, terwyl 16.1% minder as twee porsies vleis, pluimvee, vis, droë bone, eiers en neute geëet het. Ongeveer 57% van studente het klein hoeveelhede vette, olies en soetigheid ingeneem. Maaltydpatrone het getoon dat ‘n klein persentasie studente wel ontbyt oorslaan (7%). Mediaan energieinname van vroulike studente (5195kJ) was betekenisvol laer as die van mans (8943kJ). Mediaan energie- en vetinname was relatief laag terwyl koolhidraat- en proteïeninname effens hoër as die aanbevelings was. Antropometriese inligting het LMI, middelomtrek en middel-heup-verhouding ingesluit. 22.1% van vroulike studente en 12.9% van manlike studente was oormassa of vetsugtig terwyl 10.7% van vroulike en 0% van manlike studente ondermassa was. Vier studente het waardes bo die afsnypunte vir middelomtrek (vir vrouens > 88 cm en vir mans > 102 cm) en ses studente het waardes bo die afsnypunte vir middel-heup-verhouding (vir vrouens > 0.8 en vir mans > 0.9) gehad, wat ‘n risiko vir hartsiektes aandui. Die fisiese aktiwiteitvlakke van die studente is as baie aktief (59%) en aktief (39%) geklassifiseer. Ten spyte daarvan, het 68% van die studente nooit gimnasium toe gegaan nie of aan sportaktiwiteite deelgeneem nie. Van die totaal, het 10.6% gerook en ‘n mediaan van 3.5 sigarette per dag gerook. Die meerderheid (62%) het alkohol gebruik. Mediaan alkoholinname was 4.0 dae per maand en op hierdie dae (hoofsaaklik naweke) is ‘n mediaan van 3 drankies gedrink. ‘n Positiewe verband is tussen rook en alkoholinname gevind. Alkoholinname was ook betekenisvol hoër in studente wat nie op die kampus gewoon het nie. Geen betekenisvolle verskil is gevind tussen enrgieinname van studente wat op die kampus en nie op die kampus gewoon het nie. Mediaan energieinname van studente in die drie LMI kategorieë het getoon dat oormassa/ vetsugtige studente die hoogste mediaan energieinname gehad het. Die verskil tussen energieinname van die groepe was egter nie betekenisvol nie. Studente wat gerook het was ook meer geneig om ondermassa te wees. ‘n Fisies aktiewe lewenstyl en matige alkoholinname sowel as inname van ‘n gesonde dieet sal ‘n persoon se kans om ‘n normale gewig te handhaaf bevorder. Alhoewel relatief laag, moet die voorkoms van oormassa in hierdie steekproef aangespreek word. Hoë LMI op ‘n jong ouderdom is ‘n onafhanklike voorspeller van oormassa in later jare. Oormassa op ‘n jong ouderdom hou ook verband met ‘n verhoogde risiko om siektes van leefstyl, soos hartsiektes, te ontwikkel. Om hierdie redes moet fisiese aktiwiteit en gesonde eetgewoontes aangemoedig word in die stryd teen vetsug en geassosieerde siektes.
Dissertation (M.Sc. (Nutrition and Dietetics))--University of the Free State, 2006
Keywords: Nutrition -- Evaluation -- South Africa -- Free State; College students -- Nutrition -- South Africa -- Free State; College students -- Health and hygiene